DIGITAL TOOLS IN AUTONOMOUS LEARNING AND THEIR INFLUENCE ON THE ENHANCEMENT OF SOCIOLINGUISTIC COMPETENCE AMONG TECHNICAL UNIVERSITY STUDENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This research investigates the influence of digital tools in autonomous learning on the enhancement of sociolinguistic competence among technical university students. The study investigates the efficacy of diverse digital platforms, such as language-learning applications, online dictionaries, podcasts, video resources, and social media, in enhancing students' proficiency in utilizing English appropriately across various social and professional settings. A mixed-methods approach was utilized, integrating pre- and post-tests of sociolinguistic competence with questionnaires and classroom observations. The results show that students who use digital tools on their own learn a lot more about register, politeness strategies, and culturally appropriate expressions. Students also said that they were more motivated, confident, and independent when it came to using language. The study emphasizes the significance of incorporating digital tools into autonomous learning frameworks to enhance sociolinguistic competence, especially within technical education settings. Teachers are given suggestions on how to create tasks that effectively mix independent learning with digital resources to get the best results.